Integrating XR and PjBL for Social-Emotional Learning in Arts Education - Iriaji, Iriaji; Kustiawan, Usep; Yuliati, Yuliati; Sholikin, Ahmad; Leksono, Ageng Wiro; Fitri, Agem Akbar Zainul (Journal of English Language and Education, 2025)
This study developed an innovative learning model that integrates Social-Emotional Learning (SEL), Extended Reality (XR), and Project-Based Learning (PjBL) for pre-service teachers in the Cultural Arts PPG program. Employing the ADDIE framework, the research focused on the Analysis, Design, and Development phases. Twenty-four PPG students participated in the pilot phase. Findings revealed a lack of immersive learning media to support empathy, reflection, and emotion regulation in teaching practice. The designed model integrated XR-based simulations and PjBL to foster interactive and reflective learning. A Virtual Lab prototype was created featuring scenario-based SEL tasks and collaborative art projects. Expert reviews and alpha testing demonstrated increased student engagement, improved emotional awareness, and readiness to apply SEL principles in real classroom contexts. This model contributes to equipping future educators with adaptive, empathetic professional identities and highlights the potential of technology-enhanced pedagogies in teacher education.